Jian Pi Shen Shi formula alleviates hyperuricemia and related renal fibrosis in uricase‐deficient rats via suppression of the collagen‐binding pathway. (8th September 2022) - Yin, Na; Li, Xiaosi; Liu, Weichao; Qi, Yan; Wu, Runfang; Li, Zhaofu; Ying, Sai; Yang, Haihao; Gu, Qianlan; Wu, Zhao; Zou, Nanting; Duan, Weigang; et al.
Abstract: Aim: Jian Pi Shen Shi Formula (JPSSF) is a beneficial treatment for hyperuricemia and related tissue damage in the clinical setting. This study was designed to investigate its therapeutic potential and underlying mechanisms in uricase‐deficient rats (Uox −/− rats). Methods: Uox −/− rats were used to assess the therapeutic potential of JPSSF on hyperuricemia. Protein extracts from renal tissues of a Uox −/− group and a JPSSF group were analyzed using tandem mass tag labeling quantitative proteomic workflow. Collagen deposition in Uox −/− rat kidneys was analyzed by Masson trichromatic staining. The gene expression associated with collagen‐binding‐related signaling pathways in the kidneys was further explored using quantitative polymerase chain reaction assay. The protein expressions of collagen 1a1 (col1a1), col6a1, and α‐smooth muscle actin were measured by Western blotting and immunohistochemistry. Results: JPSSF significantly decreased renal function indices and alleviated renal injuries. The action of JPSSF was manifested by down‐regulation of col6a1 and interleukin‐1 receptor‐associated kinase‐like 2, which blocked the binding sites on collagen and further prevented kidney injury. The anti‐renal fibrosis effect of JPSSF was confirmed by reducing the collagen deposition and hydroxyproline concentrations. JPSSF treatment also intensely down‐regulated the mRNA and protein expressions of col6a1, col1a1, and α‐smooth muscle actin, which inhibited the function of the collagen‐binding‐related signaling pathway. Conclusion: Our results indicated that JPSSF notably ameliorated hyperuricemia and related renal fibrosis in Uox −/− rats through lowering uric acid and down‐regulating the function of the collagen‐binding pathway. This suggested that JPSSF is a potential empirical formula for treating hyperuricemia and accompanying renal fibrosis.